Restorative Justice in the Criminal Act of Rape (Analysis of the KUHP & Qanun Jinayat) - Endra Wijaya, Septeddy; Marpaung, Watni; Harahap, Arifuddin Muda (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
The crime of rape is one of the serious violations of human rights that requires effective and fair legal handling. In Indonesia, the crime of rape is regulated in the Criminal Code (KUHP) which applies nationally, as well as the Qanun Jinayat in Aceh, as an implementation of Islamic law. This study aims to analyze existing regulations related to the crime of rape in Indonesia, and to explore the potential for the application of restorative justice in handling rape cases. This study uses a qualitative method with a descriptive approach, where the researcher acts as the main instrument in collecting and analyzing data. This approach aims to explore more deeply the differences in regulations between the Criminal Code and Qanun Jinayat, and to assess their impact on the legal process and the welfare of victims. The results of the study indicate that although both regulations are firm in providing sanctions for perpetrators of rape, there are still weaknesses in protecting victims, especially in terms of mental and social recovery. Therefore, the application of restorative justice is considered important to involve victims and perpetrators in a more humane resolution process, with the aim of restoring social balance and providing opportunities for victims to recover. This study concludes that there needs to be a reform in the justice system that pays more attention to aspects of justice for victims, by combining legal sanctions and a restorative approach.